(untitled) (ARQUISUR Revista, 2025)
Extension Award - Category B The works nominated for the ARQUISUR Extension Award are those projects –whether they are in progress or executed-, whose impact can be verified, carried out by disciplinary and interdisciplinary teams made up of students, teachers and/or graduates, in order to allow the integration, articulation and strengthening of the different disciplinary areas of the Universities and developing various transferences to society of the scientific, technological and cultural knowledge, as a feedback system for academic activity. Category B includes projects approved within the framework of the call of national organizations (universities, faculties or schools, etc.) whether subsidized or not.